Mass spectrometry based proteomics for the molecular fingerprinting of Fiano, Greco and Falanghina cultivars. (June 2019) - Carpentieri, Andrea; Sebastianelli, Angelo; Melchiorre, Chiara; Pinto, Gabriella; Staropoli, Alessia; Trifuoggi, Marco; Amoresano, Angela
Abstract: The official methodologies used for the identification and comparison of vine cultivars are ampelography and ampelometry. These methodologies are essentially based on qualitative assessments or biometric dependent morphological features of the plant. The heterogeneity of cultivars and consequently the increasing demand for a more detailed product typization, led to the introduction of new methodologies for the varietal characterization. In this scenario, proteomics has already proved to be a very useful discipline for the typization of many kinds of edible products. In this paper, we present a proteomic study carried out on three cultivars of Vitis vinifera peculiar of south Italy (Campania) used for white wine production (Fiano, Greco and Falanghina) by advanced biomolecular mass spectrometry approach. Our data highlight variations in the proteomic profiles during ripening for each cultivar and between analyzed cultivars, thus suggesting a new way to outline the biomolecular signature of vines. Graphical abstract: Unlabelled Image Highlights: The increasing heterogeneity of cultivars requires a new and more detailed product molecular characterization. The proteome represents probably the best way to specifically identify and characterize a cultivar. Our results show an overall variation in terms of proteins profile for each cultivar during ripening and among different cultivars.